2021
DOI: 10.3390/ijerph18168461
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Physical Activity, Sedentary Behavior, and Anthropometric Measurements among Saudi Female Adolescents: A Cross-Sectional Study

Abstract: Overweight and obesity are becoming increasingly prevalent among children and adolescents in Saudi Arabia and are an emerging cause of non-communicable diseases (NCDs). Lifestyle factors, such as insufficient levels of physical activity and sedentary behaviors, are responsible for the increased prevalence of NCDs. This study aimed to determine the association between physical activity levels, sedentary behaviors, and anthropometric measurements in Saudi female adolescents. A cross-sectional study was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 57 publications
1
30
0
Order By: Relevance
“…Recent guidelines from the WHO, though, recommend that children and adolescents aged 6–17 years engage in at least 60 min of moderate- to vigorous-intensity physical activity every day [ 11 ]. A recent study conducted on Saudi adolescents aged 13–14 years in the city of Arar (in the northern part of the country) found a high prevalence of physical inactivity (92.7%) among the participants [ 33 ]. However, this study used a different PA questionnaire (the PA Questionnaire for Older Children) than the one used in our current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent guidelines from the WHO, though, recommend that children and adolescents aged 6–17 years engage in at least 60 min of moderate- to vigorous-intensity physical activity every day [ 11 ]. A recent study conducted on Saudi adolescents aged 13–14 years in the city of Arar (in the northern part of the country) found a high prevalence of physical inactivity (92.7%) among the participants [ 33 ]. However, this study used a different PA questionnaire (the PA Questionnaire for Older Children) than the one used in our current study.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study conducted on Saudi adolescents revealed that very high proportions of males (84%) and females (91.2%) were sedentary, defined as having more than two hours per day of screen time [ 5 ]. Adolescents from a northern city in Saudi Arabia (Arar) were found to have nearly six hours of daily sedentary time during weekdays and 7.8 h during weekends [ 33 ]. Furthermore, a large study of US adolescents showed that the prevalence of sitting while viewing screens for at least two hours per day was high and the estimated sitting time totaled 8.2 h per day among adolescents [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity implies multiple benefits, such as the prevention of cardiovascular diseases [ 12 ], better control of body weight [ 10 , 13 ], less presence of chronic pain [ 14 ], better bone density and better physical fitness [ 15 , 16 ], greater muscle strength, and lower risk of mortality [ 13 , 17 , 18 ]. In addition, at a psychological level, physical activity improves mental health and quality of life [ 8 , 19 ], reduces stress and anxiety [ 8 , 20 , 21 ], lowers the risk of depression [ 22 ], and improves the quality of sleep [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bahathig et al. [ 7 ] noted that approximately 92.7% of 399 healthy adolescent female students, aged 13–14 years, in Arar, northern Saudi Arabia, did not meet the recommended 60 min per day of moderate to vigorous PA. However, the overall average time spent in sedentary activities was 357.64 ± 86.29 and 470.51 ± 147.64 min per day on weekdays and weekends, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of body mass index (BMI) on quality of life is indisputable. Evidence has confirmed that those with normal weight have the significantly higher health-related quality of life scores than those who are obese [ 7 ]. Consequently, the American Physical Activity Guidelines [ 5 ] recommended that school-aged children and adolescents, aged 6–17 years, should practice moderate to vigorous PA for at least 1 h each day to combat overweight and obesity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%